Surgical outcome with single stage procedure for neglected congenital talipes equinovarus - Chandak, Vishal H.; Khatri, Ketan J.; Chandak, Shraddha H. (International Journal of Research in Orthopaedics, 2019)
Background: Congenital talipes equinovarus is one of the commonest congenital anomalies. In developing countries like India especially in the rural population still there are many myths, culture and awareness issues regarding this deformity. Many patients get initial treatment with casting but tend loose follow ups in this prolonged treatment. To give optimal results in these scenarios, the technique for single stage procedure which includes bony and soft tissue repair gives excellent results. Methods: In a retrospective longitudinal study, 13 children with neglected clubfeet were involved. Valid consent, clinical and radiological evaluation was done. Patients underwent single stage (bony and soft tissue) procedure described in the study. Post operatively data was collected and scoring was done as per International clubfoot study group (ICSG) at each follow ups. Results: A total 13 children out of whom 9 were male and 4 females, all having unilateral deformity were studied. The age group was between 5-22 years (mean 13.5). Postoperatively, the children were followed at 6 months intervals. As per ICSG score 10 patients had excellent results, 3 patients had good results and none had poor results. 2 patients had minor complication - delayed wound healing (2-3 weeks). Conclusions: Treatment of neglected clubfoot using single stage procedure dorsal close wedge osteotomy with soft tissue release has a high rate of good and excellent results, with low frequency of complications. It is a good alternative to conventional procedures for management of neglected clubfeet in developing countries, where compliance of patient is a problem.